2016
DOI: 10.1097/anc.0000000000000255
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Tools for Evaluation of Oral Feeding in Infants Younger Than 6 Months

Abstract: Background Feeding difficulty is common in infants less than six months old. Identification of infants in need of specialized treatment is critical to ensure appropriate nutrition and feeding skill development. Valid and reliable assessment tools help clinicians objectively evaluate feeding. Purpose To identify and evaluate assessment tools available for clinical assessment of bottle- and breast-feeding in infants less than six months old. Methods/Search Strategy CINAHL, HaPI, PubMed, and Web of Science we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…Feeding difficulties are common in young children, with reports of 25% of typically developing children and up to 80% of children with developmental delays experiencing problematic feeding . Identification of children with problematic feeding and timely referral to feeding specialty care has been limited by a lack of valid and reliable measures . The Child Oral and Motor Proficiency Scale (ChOMPS) is a valid and reliable parent‐report assessment of eating, drinking and related skills in children six months to seven years old that can be used to identify children with eating skill delays .…”
Section: Introductionmentioning
confidence: 99%
“…Feeding difficulties are common in young children, with reports of 25% of typically developing children and up to 80% of children with developmental delays experiencing problematic feeding . Identification of children with problematic feeding and timely referral to feeding specialty care has been limited by a lack of valid and reliable measures . The Child Oral and Motor Proficiency Scale (ChOMPS) is a valid and reliable parent‐report assessment of eating, drinking and related skills in children six months to seven years old that can be used to identify children with eating skill delays .…”
Section: Introductionmentioning
confidence: 99%
“…In a review of oral feeding assessment instruments for infants younger than 6 months, the findings of Pados et al . ( 2016 ) support the identification of this need. They concluded that there is a need for the development and testing of feeding assessment tools for young infants to guide optimal clinical practice.…”
Section: Discussionmentioning
confidence: 77%
“…Infants discharged with inadequate investigation into the feeding difficulties or unresolved feeding difficulties, LBW and prematurity are more at risk of developing failure-to-thrive than their term counterparts with appropriate weight for age (Browne & Ross, 2011 ). Valid and reliable assessment instruments will help clinicians to objectively evaluate feeding (Pados et al ., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pados, Park, Estrem and Awotwi ( 2016 ) found a lack of validated feeding assessment scales for infants younger than 6 months that are supported by high level evidence in a recent review. They concluded that the Early Feeding Skills Assessment Instrument (EFS) was one of the instruments that had some supportive psychometric development and testing in the neonatal population.…”
Section: Introductionmentioning
confidence: 89%
“…Other risk factors contributing to feeding difficulties were HIV exposure in utero or during delivery (30%, n = 6), respiratory distress syndrome (55%, n = 11) and hyperbilirubinaemia (55%, n = 11). Prematurity (80%, n = 16) and LBW (85%, n = 17) were the most significant known risk factors for OPD (Pados et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%